2019
DOI: 10.1103/physrevlett.122.075901
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Collapse and Second-Order Phase Transition in Thermoelectric SnSe

Abstract: Since 2014 the layered semiconductor SnSe in the high-temperature Cmcm phase is known to be the most efficient thermoelectric material. Making use of first-principles calculations we show that its vibrational and thermal transport properties are determined by huge non-perturbative anharmonic effects. We show that the transition from the Cmcm phase to the low-symmetry P nma is a second-order phase transition driven by the collapse of a zone border phonon, whose frequency vanishes at the transition temperature. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
99
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 55 publications
9
99
0
1
Order By: Relevance
“…The eutectic point of L1 (Sn) + SnSe is very close to pure Sn, and this should be one of the reasons that occasionally Sn secondary phase is formed in aqueously synthesized SnSe. Besides, SnSe has two phases, namely α‐SnSe ( T < ≈800 K) with lattice parameters of a = 11.37 Å, b = 4.19 Å, and c = 4.44 Å and a space group of Pnma and β‐SnSe ( T > ≈800 K) with lattice parameters of a = 4.31 Å, b = 11.71 Å, and c = 4.32 Å and a space group of Cmcm 3,194. In this Review, we focus on α‐SnSe phase because it has a much stable performance than β‐SnSe.…”
Section: Fundamentalmentioning
confidence: 99%
See 1 more Smart Citation
“…The eutectic point of L1 (Sn) + SnSe is very close to pure Sn, and this should be one of the reasons that occasionally Sn secondary phase is formed in aqueously synthesized SnSe. Besides, SnSe has two phases, namely α‐SnSe ( T < ≈800 K) with lattice parameters of a = 11.37 Å, b = 4.19 Å, and c = 4.44 Å and a space group of Pnma and β‐SnSe ( T > ≈800 K) with lattice parameters of a = 4.31 Å, b = 11.71 Å, and c = 4.32 Å and a space group of Cmcm 3,194. In this Review, we focus on α‐SnSe phase because it has a much stable performance than β‐SnSe.…”
Section: Fundamentalmentioning
confidence: 99%
“…For further reducing κ l , understanding the anharmonic bonding in SnSe becomes critical since it plays a significant role in determining low κ l with strong anisotropy. The anharmonic bonding can be described when an atom is forced to deviate from its equilibrium position during the phonon transportation, and the applied force is no longer proportional to its displacement, thus resulting in imbalanced phonon transport and in turn a strengthening of phonon scattering,220 which overall contributes to a low κ l 194,215,221–227. It should be noted that all bonds are anharmonic in most of the materials, but the degree of anharmonicity varies from different materials 228–233.…”
Section: Fundamentalmentioning
confidence: 99%
“…Due to the record-breaking high-temperature ZT of SnS, the Te-free Sn(S, Se) alloys are of particular interest, and experimental studies have demonstrated a reduction in the thermal conductivity of mixed compositions [12,14].Thermoelectricity is unique in that all four of the terms in the figure of merit ZT are amenable to calculation using first-principles electronic-structure methods such as density-functional theory (DFT) [18]. There have been a number of theoretical studies on existing and potential new single-component bulk thermoelectrics [6,[19][20][21][22][23], and there have recently been efforts to use high-throughput modelling to screen large numbers of compounds in a bid to identify new candidate thermoelectrics [24,25].Studying multicomponent alloy systems with first-principles methods is challenging, however, as building a realistic model requires calculations on a large number of configurations that for complex systems with lowsymmetry unit cells can easily approach the cost of a screening study [26]. Ektarawong and Alling used a firstprinciples cluster expansion method to study the Pnma Sn(S 1-x Se x ) system and confirmed the stability of the mixed phases at finite temperature [27].…”
mentioning
confidence: 99%
“…Thermoelectricity is unique in that all four of the terms in the figure of merit ZT are amenable to calculation using first-principles electronic-structure methods such as density-functional theory (DFT) [18]. There have been a number of theoretical studies on existing and potential new single-component bulk thermoelectrics [6,[19][20][21][22][23], and there have recently been efforts to use high-throughput modelling to screen large numbers of compounds in a bid to identify new candidate thermoelectrics [24,25].…”
mentioning
confidence: 99%
“…The SSCHA is a quantum variational method that efficiently calculates anharmonic free energies and phonon frequencies in a non-perturbative way. This approach has been very successful for calculating phonon frequencies and superconducting properties in hydrogen-rich materials, as well as in systems undergoing charge density wave (CDW) transitions, ferroelectrics, and thermoelectrics [23,[27][28][29][30][31][32]. For the muon, the SS-CHA is variational in the muon (free) energy, with this energy evaluated stochastically from forces and energies calculated at a sufficient number of random muon configurations.…”
Section: Introductionmentioning
confidence: 99%